Pengaruh product quality, price dan advertisement terhadap purchase decision smartphone merek samsung dan iphone - Valeri Kusumadewi , Camila; Farhan Aditya, Achmad; Kristaung, Robert (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
The purpose of this study was to determine what factors influence Purchase Decision, with the variables used being Product Quality, Price and Advertisement. In this study, using purposive sampling technique with 32 samples with the criteria that consumers use Samsung and iphone brand smartphones. The tool used in this research is the Structural Equation Model (SEM) which is run by the AMOS program. The results of this study indicate that there is a positive effect of Product Quality on Purchase Decision, there is no positive effect of Price on Purchase Decision, there is no positive effect of Advertisement on Purchase Decision.